Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00198-014-2833-z
|View full text |Cite
|
Sign up to set email alerts
|

Women with severe obesity and relatively low bone mineral density have increased fracture risk

Abstract: Women with obesity who have the lowest BMD values, despite these being almost normal, have an elevated risk of fracture compared to those with higher BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
3
13
0
1
Order By: Relevance
“…Sarcopenic and dynopenic obese individuals appear to be at a greater risk for lower BMD and higher fracture risk than obese individuals with normal muscle mass and strength (Scott, et al 2016). This interpretation is consistent with studies reporting that obese osteopenic individuals are at a higher fracture risk compared to normal weight osteopenic individuals (Cawsey, et al 2015). Finally, sarcopenia and dynopenia could result in higher strain levels during a fall or increased fall frequency.…”
Section: Scaling Bone Mass To Body Weightsupporting
confidence: 92%
“…Sarcopenic and dynopenic obese individuals appear to be at a greater risk for lower BMD and higher fracture risk than obese individuals with normal muscle mass and strength (Scott, et al 2016). This interpretation is consistent with studies reporting that obese osteopenic individuals are at a higher fracture risk compared to normal weight osteopenic individuals (Cawsey, et al 2015). Finally, sarcopenia and dynopenia could result in higher strain levels during a fall or increased fall frequency.…”
Section: Scaling Bone Mass To Body Weightsupporting
confidence: 92%
“…44 However, other studies point to an inverse relationship with BMD. 45, 46 These conflicting observations highlight the complexity of the relationship, an observation that is also seen in the mouse literature. For example Li et al , 47 studying multiple inbred mouse strains, concluded that the relationship between BMD and body composition, particularly fat mass, is dependent on the diet used.…”
Section: Discussionmentioning
confidence: 94%
“…When evaluating the influence of increasing body fat in elderly patients with obesity, it was found that greater adiposity and adipokine levels were associated with reduced lean mass, lower BMD, and increased fracture risk. 31 A clinical study assessing 400 obese women in relation to BMI and fracture risk found that even obese women with almost normal BMD had an elevated risk of fracture compared with obese women with higher BMD scores, 32 , suggesting that BMI does not always relate to fracture risk. Whether BMD is a predictor of fracture risk is still debatable.…”
Section: Impact Of Obesity On Musculoskeletal Tissue Systemsmentioning
confidence: 99%